2022
DOI: 10.1002/ptr.7426
|View full text |Cite
|
Sign up to set email alerts
|

A review on the potential use of natural products in overweight and obesity

Abstract: With the increase in unhealthy lifestyles, obesity is increasingly common, which could cause many metabolic diseases. In recent research, natural product extracts have shown tremendous potential antiobesity effects via different mechanisms. In this review, we focused on widely adopted extraction methods, bioactive ingredients types, and antiobesity mechanisms of natural product extracts in the recent reports. The extraction methods include solid-liquid extraction, microwave-assisted extractions, and supercriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 173 publications
(273 reference statements)
0
5
0
Order By: Relevance
“…It was reported that the PI3K-AKT signaling pathway may inhibit the gluconeogenesis pathway and reduce the output of glucose, thereby exerting a hypoglycemic effect in db/db mice [ 26 ]. Previous studies have reported that Zanthoxylum bungeanum extract may play a hypoglycemic effect by downregulating PGC-1 α in the liver [ 27 ]. Inflammation is closely related to the occurrence and development of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the PI3K-AKT signaling pathway may inhibit the gluconeogenesis pathway and reduce the output of glucose, thereby exerting a hypoglycemic effect in db/db mice [ 26 ]. Previous studies have reported that Zanthoxylum bungeanum extract may play a hypoglycemic effect by downregulating PGC-1 α in the liver [ 27 ]. Inflammation is closely related to the occurrence and development of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies report that these products may exert effects through multiple mechanisms, including appetite suppression, interfering with nutrient absorption, decreasing adipogenesis, increasing energy expenditure (thermogenesis), modifying the intestinal microbiota, composition and increasing excretion of fecal fat. [53,54] Studies on the anti-obesity potential of M. subnitida products are scarce, and this effect was investigated only for its honey.…”
Section: Anti-obesity Activitymentioning
confidence: 99%
“…However, compared to weight-loss drugs and bariatric surgery, dietary intervention is often considered more convenient, safe, and sustainable. 11 Recently, polyphenolic compounds such as anthocyanins have shown considerable potential anti-obesity effects through different mechanisms. Anthocyanins are widely present in various plants, including sour cherry, cranberry, black beans, blueberry, sweet cherry, strawberry, and pomegranate.…”
Section: Introductionmentioning
confidence: 99%